Delayed epidural hematoma after mild head injury - Radulović Danilo; Janošević Vesna; Rakić Miodrag; Đurović Branko; Slavik Eugen; Lakićević Novak (Vojnosanitetski Pregled)
Background. Traumatic delayed epidural hematoma (DEH) can be defined as insignificant or not seen on the initial CT scan performed after a trauma but seen on the subsequent CT scan as a “massive” epidural bleeding. Case report. We presented two cases of traumatic DEH after mild head injury. Both patients were conscious and without neurological deficit on the admission. Initial CT scan did not reveal intracranial hematoma. Repeated CT scan, that was performed after neurological deterioration, revealed epidural hematoma in both cases. The patients were operated with a favorable surgical outcome. Conclusion. Traumatic DEH could occur in the patients with head injuries who were conscious on the admission with a normal initial CT scan finding. Early detection of DEH and an urgent surgical evacuation were essential for a good outcome.